2001
DOI: 10.1097/00054725-200111000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Crohn's Disease: Review of the Clinicopathologic Features and Therapy

Abstract: Crohn's disease in the proximal region of the digestive tract is uncommon. Better diagnostically procedures and more careful histologic examination has led to a higher detection of proximal Crohn's disease. The diagnosis is based on symptoms, endoscopy with serial sections, or double contrast radiography. The most common histologic finding for this diagnosis are granulomas in the mucosa in Helicobacter pylori-negative patients, but the granulomas are not always frequently detected. Endoscopic lesions in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
102
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(114 citation statements)
references
References 80 publications
1
102
0
4
Order By: Relevance
“…Uncontrolled series have reported symptomatic improvement for upper GI CD with use of proton pump inhibitors (118) and other systemically active therapies, such as systemic corticosteroids, azathioprine, 6-mercaptopurine, methotrexate, in iximab, adalimumab and certolizumab pegol, are used in a manner similar to their use in patients with moderate to severely active ileal or colonic disease (see below). Similarly, there is no evidence base for recommendations regarding the treatment of jejunoileitis that is o en complicated by multifocal stricturing with resultant small bowel bacterial overgrowth and other nutritional consequences (119,120) . Rotating antibiotics can be e ective in the treatment of small bowel bacterial overgrowth, and supportive nutritional therapies (see below) are frequently required.…”
Section: Mild To Moderate Active Diseasementioning
confidence: 99%
“…Uncontrolled series have reported symptomatic improvement for upper GI CD with use of proton pump inhibitors (118) and other systemically active therapies, such as systemic corticosteroids, azathioprine, 6-mercaptopurine, methotrexate, in iximab, adalimumab and certolizumab pegol, are used in a manner similar to their use in patients with moderate to severely active ileal or colonic disease (see below). Similarly, there is no evidence base for recommendations regarding the treatment of jejunoileitis that is o en complicated by multifocal stricturing with resultant small bowel bacterial overgrowth and other nutritional consequences (119,120) . Rotating antibiotics can be e ective in the treatment of small bowel bacterial overgrowth, and supportive nutritional therapies (see below) are frequently required.…”
Section: Mild To Moderate Active Diseasementioning
confidence: 99%
“…We identified 7 patients with the diagnosis of CD in the upper gastrointestinal tract, which is 1.04% of the total hospitalizations due to CD. According to the literature, the appearance of CD in the upper gastrointestinal tract is at the level of 0.5-13% [8,9].…”
Section: Methodsmentioning
confidence: 99%
“…In the clinical view, dysphagia and weight loss were the most typical symptoms in the first case, whereas in the third heartburn and odynophagia were observed. Endoscopy of the upper gastrointestinal tract can reveal the following lesions in the oesophageal region: irregular reddening or aphthous, or swollen folds of the mucous membrane, deep linear ulcerations located in the whole oesophageal mucous (which in fact is extremely rare) and strictures or fistulas [9,17]. Yekebas et al reported a case of oesophageal perforation due to a stricture of the distal oesophagus as the primary manifestation of CD [17].…”
Section: Leki Stosowane W Terapii Choroby Leśniowskiego-crohnamentioning
confidence: 99%
See 2 more Smart Citations